ANALISIS PELAKSANAAN KONSELING INDIVIDUAL DI SMP NEGERI 9 PONTIANAK - Vitaria Esther Brigitha; Yuline Yuline; Luhur Wicaksono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aimed to determine the implementation of individual counseling at SMPN 9 Pontianak due to the unsuccessful resolution of counselees’ problems. Descriptive research with qualitative method was employed in this study. Interview, observation, and documentation were used as the data collection technique. The subjects in the study were the counseling teacher and 3 students. The findings showed that the indicators such as rapport, problem representation, problem interpretation, contract negotiation, exploration of the problem, revaluation, good relation maintenance, conclusion making, action planning, action plan evaluation, and meeting continuation have not been implemented completely. The indicators that have not been implemented were (1) Difficulty in building good relations with all counselees, (2) the counselees engagements were low in the activity, (3) the counselor did not regulate the time contract in activities, (4) the counselor did not pursue the development of potential and empathy in the exploration of the problem, and (5) ineffective counseling activities due to the lack of meeting continuation. Accordingly, the teacher is demanded to build better communication with the counselees, offer better understanding regarding individual counseling activities, make the time contract, and attempt to explore the counselees' potentials. Keywords: Individual counseling implementation, Individual counseling.